Regionalización de las migraciones residenciales interurbanas en Chile en el período 1997‑2002 - Severino Escolano‑Utrilla; Jorge Ortiz-Véliz; Rodrigo Moreno-Mora (Confins)
Interurban residential changes are expressions of the interactions between cities of an urban system. Migratory flows shape a unique and organized network that emerges from the practices of migrants. An applied combination of network analysis and spatial analysis methods to census microdata has allowed characterizing the structure of the network of interurban migratory flows in Chile in the period 1997-2002. The results obtained show that interurban residential migrations shape a network of heterogeneous flows in terms of their magnitude and spatial extend. Nevertheless, their combination build a hierarchical and very stable structure, composed of groups of cities with strong reciprocal migratory interconnections. Geographical proximity is one of the most important factors shaping this structure, in addition to the territorial dynamics of the economy and the distribution and hierarchy of transport and communications infrastructures.